Ocular surface disorder in pterygium: Role of conjunctival impression cytology - Bandyopadhyay Ranjana; Nag Dipanwita; Mondal Santosh; Gangopadhyay Susmita; Bagchi Ketaki; Bhaduri Gautam (Wolters Kluwer Medknow Publications, 2010)
Objective: To study ocular surface abnormalities in patients with pterygium, conjunctival impression cytology was explored as a tool for the assessment of the cytological changes. Materials and Methods: A comparative case control study was undertaken to evaluate the ocular surface disorders in pterygium. Fifty cases of pterygium and 50 age and sex-matched controls were analyzed for the presence of local tear film abnormalities as assessed by the tear film break up time and Schirmer test. The spectrum of changes in cytomorphology was studied in detail using conjunctival imprint cytology. Results: Tear film break-up time and Schirmer′s strip wetting were found to be significantly different in study and control groups. Studying the cytomorphology of the conjunctival imprint smears, reduced cellularity and squamous metaplasia of different grades was observed more frequently in patients compared to controls. On overall grading of cytological changes, statistically significant difference was noted between the study and control groups (P value 0.00172). Conclusion: From the present study we can suggest that aqueous tear film deficiency leading to ocular surface disorder brings about a change at the cytological level, and ocular surface disorders found in pterygium can be interpreted by conjunctival impression cytology.